Collaborative Learning Strategies in Algebra: Effects on Grade 8 Students’ Conceptual Understanding - Mohammad, Amerah S.; Anda, Asgar M. (Education, Science, and Technology International Conference, 2025)
Collaborative learning strategies have emerged as effective approaches in fostering students’ conceptual understanding, particularly in mathematics, by encouraging active participation, peer interaction, and shared problem-solving. This study aimed to investigate the effect of collaborative learning strategies on students’ conceptual understanding in algebra. The study used a quasi-experimental design using a pretest and posttest control group design. The participants were Grade 8 students of Ampaso Memorial National High School at Binidayan, Lanao del Sur. The findings showed that before the intervention, the control group had a mean score of 13.00, while the experimental group had a mean score of 13.35. The t-value of .33 and p-value of .74 indicate no significant difference in conceptual understanding between the two groups. After the intervention, both groups improved, but the experimental group showed a greater increase with a mean score of 28.81. The t-value of 2.21 and p-value of .032 indicate a statistically significant difference on the control and experimental groups. The findings of this study suggest that collaborative learning strategies had a positive effect on students’ conceptual understanding. It is recommended that educators incorporate collaborative learning strategies into algebra instruction to enhance conceptual understanding.